Analisis Faktor Abiotik dan Karakteristik Mangrove di Kawasan Hutan Mangrove Langsa - Adi Hartono; Enni Halimatussadiyah Pakpahan; Hasbi Assidiqi Nasution; Siti Mutia; Setyawati; Nurshita Dwi Nanda (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aimed to analyze the abiotic factors and morphological characteristics of mangrove vegetation in the Langsa Mangrove Forest area, Aceh. The research was conducted through direct field exploration using descriptive–quantitative methods, involving the observation of vegetative and generative organs of mangrove species and measurement of environmental parameters such as salinity, pH, temperature, and total dissolved solids (TDS). Morphological data were documented and identified using field guides, while abiotic parameters were measured in situ using standard instruments (pH meter, salinometer, DO meter, and thermometer). The results identified eleven mangrove species, including Rhizophora mucronata, R. Apiculata, R. Stylosa, Avicennia alba, Kandelia obovata, Ceriops tagal, Xylocarpus granatum, Acanthus ilicifolius, Scyphiphora hydrophyllacea, Acrostichum aureum, and Casuarina equisetifolia. Each exhibited distinctive morphological adaptations such as prop roots, pneumatophores, thick waxy leaves, and viviparous fruits that support survival in high-salinity and anaerobic conditions. The abiotic data showed an average salinity of 0.92% (≈8.82 ppt), water pH 6.68, soil pH 5.74, temperature 29.18 °C, and electrical conductivity 17.25 mS/cm—values within the optimal range for mangrove growth. These findings indicate that the Langsa mangrove ecosystem remains stable and ecologically healthy, supporting high species diversity. The study concludes that the interaction between abiotic conditions and plant morphology determines the ecological balance of the Langsa mangrove habitat, highlighting the importance of sustainable management and conservation of this coastal ecosystem. Keywords: abiotic factors, environmental parameters, Langsa Mangrove Forest, mangrove ecology, morphological adaptation